Dispersion modeling and health risk assessment of VOCs emissions from municipal solid waste transfer station in Tehran, Iran - Sarkhosh, Maryam (J Environ Health Sci Eng, 2017)
BACKGROUND: The waste transfer stations (WTSs) is one of the most important factors affecting on environment and human health. This research is aimed to evaluate health risk of VOCs among WTS personnel and provide a model for dispersion of VOCs. The Air Pollution Model (TAPM) is able to simulate WTS emissions dispersion over each town. RESULT: GC-MS was used to analysis collected gas samples to detect and estimate carcinogenic and non-carcinogenic VOCs health risks. The total lifetime cancer risk values for the all personnel (3.30E-05), was more than acceptable limit (1.00E-06). Furthermore, hazard ratio (HR) of 1,2,3-trimethylbenzene, 1,3-dichloropropane, toluene, m,p-xylene and ethylbenzene were 3.7, 1.9 E-01, 4.4 E-03, 5.5 E-02 and 1.5 E-03, respectively, and total HR of the mentioned compounds were more than accepted limit (HR < 1.00). IOA is 0.85 and RMSE is 2.16 and TAPM has a good performance. The VOCs level is considerable in 1600 m far from the WTS particularly in summer that require more attention. CONCLUSION: The exposure to VOCs was at a high level in WTS, and some controlling strategy should be used for decreasing the pollution and protecting the citizens and personnel against non-cancerous and cancerous risks.